On Cultural Political Economy: A Defence and Constructive Critique. Issue 6 (2nd November 2021) - Sau, Andrea
ABSTRACT: This article explores the relationship between economic and political realms by reference to the Marxist conception of the economy as the 'motor of history'. The discussion is framed through a recent debate around Cultural Political Economy (CPE) and its efforts to keep Marx's materialist premises without falling into economic reductionism, or 'bend the stick too far' into the opposite direction and fall into 'constructivism'. Despite the efforts to avoid said extremes, CPE have been criticised for being both reductionist and constructivist This piece will defend CPE against the above charges while also highlighting some unresolved tensions within the method. I will then propose ways to resolve said tensions as well as providing the means of extending the scope of CPE to deal with political issues going beyond the economic realm, without losing sights of their connections to regimes of accumulations and resulting material needs and grievances of various groups. I will argue that this further development is necessary to analyse an increasingly unpredictable political landscape where tribal enmities and xenophobic feelings are returning to mainstream politics.